Survey on the Research Challenges of Radio Resource Management in LTE-A and the Current Proposed Solutions for these Challenges - Al-Jaradat, Huthaifa; Sandrasegaran, Kumbesan (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Long Term Evolution-Advanced (LTE-Advanced) has been recently submitted by the 3rd Generation Partnership Project (3GPP) to the International Telecommunication Union (ITU) as one of the candidates 4G technologies. LTE-Advanced is expected to outperform its predecessor (i.e. LTE) by providing data rate up to 1Gbps and 500 Mbps in the downlink and uplink directions, respectively, also by supporting higher speed mobility (i.e. 500 km/h). In order to allow such advances in the performance, Radio Resource Management (RRM) must be effectively utilized. This paper studies the technical challenges associated with some of the RRM tasks (including Packet scheduling, interference management and handover control), in addition it presents from the open literature some of the proposed solutions to these technical challenges.